Ligation of fistulas of rectum in intersphincteric layer: the pilot study - M. N. Chekanov; A. M. Chekanov; I. G. Verner (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2012)
Aim of investigation. Ligation of fistulous tract in intersphincteric layer (Ligation of Intersphincteric Fistula Tract – LIFT) – is a new method of surgical treatment of trans- and extrasphincter fistulas. It is obviously important to estimate LIFT results according to original experience and literature data.Material and methods. LIFT technique is described. Overall 19 patients were operated: men – 11, women – 8, mean age 48±13 years (26 to 74 years). Ten patients had anterior transsphincteric fistula, anterior extrasphincter — 4, posterior transsphincteric – 1, posterior extrasphincter – 4.Results. The median of term of follow-up was 42 wks (3 to 105 wks). The relapse of fistula was is marked in 2 patients. No disorders of fecal continence were revealed. At the moment of article submission literature data on LIFT results in 353 patients were available. The relapse rate at follow-up for 20–30 wks was 26%.Conclusion. LIFT – is the simple, safe and effective method of treatment trans- and extrasphincter fistulas of the rectum.